Complete defect in PA-PLA1α secretion function leading to autosomal recessive woolly hair and hypotrichosis: insights from a novel compound heterozygous LIPH variant study in a Chinese pedigree - Zhang, Xinyue; Guo, Kexin; Liu, Jiawei; Yang, Xueting; Zhang, Rui; Wang, Rongrong; Ma, Donglai; Zhang, Xue (Frontiers in Genetics, 2025)
Autosomal recessive woolly hair/hypotrichosis (ARWH) is a rare inherited hair disease. In this study, we report a 31-year-old Chinese female with the characteristic clinical features of woolly hair and hypotrichosis. Through whole-exome sequencing (WES), we identified a novel missense variant (NM_139248.3: c.530T>G: p.Leu177Arg) and a previously reported missense variant (c.742C>A: p.His248Asn) of LIPH in the patient. TA cloning demonstrated that these variants were located on different alleles, supporting an autosomal recessive inheritance pattern. In silico tools predicted the novel variant to be disease-causing, likely reducing the stability of PA-PLA1α, the protein encoded by LIPH. PA-PLA1α, a member of the AB hydrolase superfamily and the lipase family, functions as a secreted protein to perform its hydrolytic and catalytic activities. Through a secretion assay, we observed that the novel missense variant c.530T>G almost abolished the secretion of the variant protein compared to the control (p < 0.0001). The direct blocking of secretion has only been reported in two variants in previous studies. This means that it is likely to result in the complete loss of its hydrolytic function, which will eventually lead to the disease. Notably, all the variants that directly stopped secretion happened when the normal amino acid was replaced by arginine. This suggests that the arginine substitutions may be closely linked to making secretion less effective. Our study not only elucidates the genetic underlying in a Chinese patient with woolly hair but also clarifies its pathogenic mechanism. These discoveries may facilitate the advancement of future diagnostic and treatment approaches.